Generación de biogás a partir de efluente doméstico y lixiviado del relleno sanitario de Encarnación (Journal on studies and research of academic knowledge, 2018)
The society development is based on the consumption of large amounts of energy. The energy that circulates through the ecosystems and allows life comes ultimately from the sun, although most of the energy that is consumed comes from natural resources existing on our planet, mainly from coal and oil, but due to the excessive use of these fuels has produced a negative environmental impact on the biosphere, polluting air, water and soil. Attending this situation, has emerged this research, which main objective was to evaluate the  feasibility of biogas generation, in a biodigestion system, from a mixture of domestic wastewater and leachate generated in the sanitary landfill of Encarnación city. For this, have been tested three mixtures of effluent - leached; 70 -30%, 60 - 40% and 50 - 50% respectively, to define which of the three generates the greatest amount of gas. The highest production was recorded from the mixture 70 - 30% with a value of 1455 ml, with a hydraulic retention time of 30 days. This result reflects that it is feasible to generate biogas from domestic effluent and leached, harnessing the waste generated by the population, reducing the use of fossil fuels and avoiding adverse effects on the environment.
Keywords: Biogas; biodigestion; domestic effluent; leachate